Estudio de factibilidad para el establecimiento de una empresa forestal en el cantón Pangua, provincia de Cotopaxi. - Barrionuevo Benitez, Pablo Simón (2009)
The present feasibility study of a Forestal Company, was made in the average and high zone of the Pangua corner, province of Cotopaxi, in an altitude that goes from the 1,500 to the 3,000 m.s.n.m. The results were: One determined the forest companies that require plántulas in the Pangua Corner, of that excels 96.08% of this demand corresponds to organizations of farmers of the zone. With respect to the supply I have been determining three (3) forest companies that supply plántulas in the zone, two of them, (67.67%) is in the market for three years. The characteristics of plántulas that produce determined that two of them (66.67%) sell plántulas exotic and as soon as one (33.33%) produces plántulas native. The fixed investment of the tangible fixed assets and the intangible fixed assets, the same one that ascend to the amount of 30808.40 dollars. The capital of operation for the three first months of operation ascends to the amount of 8249.10 dollars. For the operativity of the project 50% that is to say, 32,953 will be contributed with equity capital, 75 dollars and for the rest it anticipates a hypothecating credit to 3 years terms in a banking organization of the locality. The costs that will take place in the operativity of the project, for their greater control we have divided the costs of operation in fixed costs which they oscillate in $21.547, 16 and the variables in $ 18,476, 40. The budget of income by concept of annual sales ascends to the amount of $ 50085.00, for the first year. The net utility after to discount to all the costs and expenses that incur every year of life utility of project For the first year utility it is of $ -2,655, the 65 flow of box generated for the first year is 4,834, 44 dollars. The level of monetary balance of the first year is of $ 21,546, 79; the production of plántulas minimum is 61,562 plants. The relation benefit cost gave like result 2,67. The internal rate of return is 21, which is superior to the interest rate of the market. VAN also presented/displayed a positive value what means the updated liquid return generated by the project